Fruit splitting in 'Nova' hybrid mandarin in relation to the anatomy of the fruit and fruit set treatments - García-Luis, Amparo (2012)
Fruil splining in the mandarin orange cultivar ‘Nova’ is related lo lhe prescnce of an open stylar end in lhe fruit This opening arises from a cavily present at lhe base of lhe style, and is formed in a varjable proportion of fruits. The edis at lhe boltom of lhis styie cavily form a rind-lilce lissue which develop into a navel struclure. The size ofthis nave! is larger in open-slylar end bearing fruits and, according!y, ia sp!it fruil. The number of split fruil per tree is unrelaled to lhe number of fruit set. The application of gibberel!ic acid (GA,) has a variable effect on set and splitting depending on its timing. This hormone increases fruit sp!ilting when app!ied aI flowering, bel reduces it when applied shortly afler lhe end of lhe June drop. Ilhas on!y a minor effect on fruit seI.